Investigating the Challenges Faced by Semester Six Students in Learning English Syntax: A Case Study at Ibn Tofail University, Morocco - Rachida M'chaar; Abderrazak El Kemma; Bendaoud Nadif (Amandemen: Journal of Learning, Teaching and Educational Studies, 2026)
This study examines the challenges faced by sixth-semester students at Moroccan Public University in learning English syntax. Syntax, as a key area of linguistics, is crucial for understanding sentence structure and grammatical accuracy. Despite its importance, students often struggle due to the abstract concepts, specialized terminology, and fast instructional pace. Utilizing a mixed-methods approach with questionnaires and open-ended questions, the study involved 104 students from the English department . The findings reveal significant obstacles such as weak foundational knowledge, limited practical exercises, and the complexity of syntactic theories. In particular, mastering X-bar theory is challenging; common errors include confusing complements, adjuncts, and specifiers when assigning roles within the hierarchical tree structure. Additionally, students find it difficult to comprehend how auxiliaries move within the tree and how transformations like T-to-C movement function derivationally. The cognitive load increases as learners navigate layered projections (X, X′, XP) and distinguish between constituents, especially when movement disrupts the expected linear order. These results highlight the need for learner-centered teaching strategies that simplify and actively engage students with complex syntactic topics such as X-bar theory and syntactic movement, aiming to improve learning outcomes in syntax.